Perencanaan Struktur Fasilitas Olahraga Di Lingkungan PT. Solusi Bangun Indonesia Pabrik Tuban - Dwi Yulistiyanti, Liana; Setyobudi, Risang; Maududi, Maududi (Lembaga Dongan Dosen, 2025)
Sport has an important role in improving the quality of human life, this research aims to design an optimal sports facility structure in the environment of PT Solusi Bangun Indonesia, Tuban Factory. The author refers to SNI 1729: 2020, SNI 1727: 2020, SNI 1726: 2019, and SNI 2847: 2019 based on STAAD.Pro Connect Edition software to meet the technical and safety demands of the building. The methods used in this research include literature study, and data analysis. Literature studies are used to understand the basic concepts and structural comparisons with warehouse/warehouse buildings that have long spans found in the PT Solusi Bangun Indonesia environment. The results showed that the structure of this sports facility has main column dimensions with H 400x400x13x21 steel profiles, WF main beams. 300x150x6.5x9 and truss using profile WF. 400x200x8x13, With this structurally safe and optimal sports facility planning, it is hoped that PT Solusi Bangun Indonesia Tuban Factory can build sports facilities efficiently both in cost and time schedule. Keywords: Structure Planning, Sports Facility, STAAD.Pro Connect Edition, PT Solusi Bangun Indonesia,